Bureaucracy in nation-building and development : a fifty years profile - Bava, Noorjahan (2001)
Following a description of the developmental paradigm of our democracy, the author attempts an analytical assessment of India's developmental performance since Independence, drawing a comparison of the scenario prevaling then and now on the basis of relevant bench-mark data reflecting on the quality of life. She then attempts a brief comparison between India and some Asian nations which are presently on a faster track of development to deduce her conclusions. Before winding up the discussion, she also attempts a brief evaluation of our bureaucracy as a catalyst of change and nation-building. - Reproduced.
Keywords: Nation building; Bureaucracy